Bronchoesophageal fistula: An unusual manifestation of lung cancer. (2022) - Smith, Chelsea; Bannon, Mark; Ashraf, Adrita; Kaushik, Prashant; Marak, Creticus
Abstract: Bronchoesophageal fistula (BEF) is a rare condition caused by a fistulous connection between the bronchus and the esophagus. BEF can be acquired or congenital; congenital BEFs are rarely encountered in adults. Acquired BEF can be due to either a benign or a malignant process. Acquired BEF due to primary lung cancer is a life-threatening and usually a terminal complication. Unlike tracheoesophageal fistula, this condition is much rarer. Patients usually present with symptoms related to recurrent aspiration. Barium esophagogram is the initial diagnostic modality of choice. Treatment is primarily palliative. We are presenting a case of a bronchoesophageal fistula caused by non-small cell lung cancer that was successfully treated with concurrent chemoradiation therapy.